Dramatically Enhanced Ambient Ammonia Electrosynthesis Performance by In‐Operando Created Li–S Interactions on MoS2 Electrocatalyst. Issue 14 (20th February 2019) - Liu, Yanyan; Han, Miaomiao; Xiong, Qizhong; Zhang, Shengbo; Zhao, Cuijiao; Gong, Wanbing; Wang, Guozhong; Zhang, Haimin; Zhao, Huijun
Abstract: The Haber‐Bosch process can be replaced by the ambient electrocatalytic N2 reduction reaction (NRR) to produce NH3 if suitable electrocatalysts can be developed. However, to develop high performance N2 fixation electrocatalysts, a key issue to be resolved is to achieve efficient hydrogenation of N2 without interference by the thermodynamically favored hydrogen evolution reaction (HER). Herein, in‐operando created strong Li–S interactions are reported to empower the S‐rich MoS2 nanosheets with superior NRR catalytic activity and HER suppression ability. The Li + interactions with S‐edge sites of MoS2 can effectively suppress hydrogen evolution reaction by reducing H* adsorption free energy from 0.03 to 0.47 eV, facilitate N2 adsorption by increasing N2 adsorption free energy from –0.32 to –0.70 eV and enhance electrocatalytic N2 reduction activity by decreasing the activation energy barrier of the reaction control step (*N2 → *N2 H) from 0.84 to 0.42 eV. A NH3 yield rate of 43.4 μg h −1 mg −1 MoS2 with a faradaic efficiency (FE) of 9.81% can be achieved in presence of strong Li–S interactions, more than 8 and 18 times by the same electrocatalyst in the absence of Li–S interactions. This report opens a new way to design and develop catalysts and catalysis systems. Abstract : The ambient NH3 electrosynthesis performance of MoS2 is dramatically enhanced by in‐operando created Li–S interactions through effectively suppressed hydrogen evolution reaction activity at S‐edge/Mo‐edge sites, and simultaneously increased N2 adsorption capability and boosted N2 reduction reaction catalytic activity on Mo‐edge sites. The reported in‐operando formation of catalytic active structures via catalyst–electrolyte interactions opens a new way to develop catalysts and catalysis systems.